DESIGNING AND MANUFACTURING MONITORING STATION FOR EARLY DETECTION AND TRANSMITTING FOREST FIRE INFORMATION - Quang Bao, Tran; Ha An, Mai; Ngoc Hoan, Le (Journal of Forestry Science and Technology, 2016)
This paper represents designing results of forest fire monitoring equipment developed by researchers from Vietnam National University of Forestry. The function of equipment is to automatically detect forest fire and to transmit this information to forest owners and managers. The system used fire detection algorithm from IP camera and applied geospatial technology to manage forest fire, early detect hotspot and transmits information for forest fire fighting. The system includes 01 IP camera connected to the Internet via 3G signal, 01 software for controlling and analyzing data. To evaluate the possibility of fire detection and the accuracy of the information transmitted by the model, the authors conducted a control forest fire at different spatial location and levels of fire intensity. This is an automatic system for early detection of forest fires with high precision, replacing manually monitoring in forest management. It helps to prevent forest fires spreading and minimizing the damage caused by forest fires.